Sexual attitudes and their relationship with state-rate anxiety in university students of Metropolitan Lima - Oyola Villarroel, Pedro Pablo (2019)
This study aims to find the correspondence between sexual attitudes and state-trait anxiety, as well as find differences in the different dimensions of sexual attitudes with state-trait anxiety. The sample consisted of 215 university students from a particular university in Metropolitan Lima. For data collection, the Inventory of Attitudes towards Sexuality and the State-Trait Anxiety Inventory (STAIC) adapted to the Peruvian context were used. The results showed that there is a direct relationship between sexual attitudes and state anxiety in the dimensions of liberalism and sexual excitability, however sexual attitudes related to sexual puritanism are less than state anxiety. In this sense, those evaluated who show higher levels of anxiety as a state, tend to maintain greater attitudes of liberalism and sexual excitability, but lower levels of sexual puritanism. On the other hand, a direct relationship between sexual attitudes and trait anxiety was found in the dimensions of sexual puritanism, sexual neocriticism and sexual insecurity, but lower levels of sexual liberalism and sexual excitability. In this sense, those evaluated with higher levels of anxiety as a trait tend to maintain greater attitudes of sexual puritanism, sexual neuroticism and sexual insecurity, but lower levels of sexual liberalism and sexual excitability.